Hygroscopicity of ultrafine particles containing ammonium/alkylaminium sulfates: A Köhler model investigation with correction of surface tension. (1st February 2023) - Liu, Liyuan; Li, Hui
Abstract: Insights into the hygroscopicity of nanoparticles is critically important in determining their growth and subsequent climate implications. A significant knowledge gap in the traditional Köhler (TK) model is the lack of size dependence of physicochemical properties of nanoparticles. Here, we present the modified Köhler curves of nanoparticles containing ammonium sulfate (AS) and alkylaminium sulfates (AASs), including monomethylaminium sulfate (MMAS), dimethylaminium sulfate (DMAS), and trimethylaminium sulfate (TMAS), by considering the curvature-correction of surface tension ( σ ) obtained from polarizable molecular dynamic (MD) simulations. It is found that sulfates can cause a non-monotonic relation between σ and droplet size with a maximum at several nanometers. The modified Köhler curves demonstrate that, for sulfate particles with diameters over 10 nm, accounting σ -correction can apparently affect the inverse of critical supersaturation ( S c − 1 ), but still give the consistent S c − 1 order with the model without σ -correction ( S c − 1 (AS) >  S c − 1 (MMAS) >  S c − 1 (DMAS) >  S c − 1 (TMAS)). While for ultra-small particles ( d  = ∼3 nm), the curvature correction of σ is much more significant, which even alters the order of S c − 1 ( S c − 1 (MMAS) ≈  S c − 1 (DMAS) >  S c − 1 (AS) >  S c − 1 (TMAS)). The present study shows that the curvature correction of surface tension is necessary to accurately predict the hygroscopicity of nucleation mode particles, and MMAS/DMAS-containing nanoparticles can demonstrate easier water-uptake than that of AS-containing nanoparticles with ∼3 nm diameter, thereby leading to higher growth rate and stronger climate impacts. Graphical abstract: Image 1 Highlights: Modified Köhler curves for ammonium/alkylaminium sulfate nanoparticles are derived. The importing of curvature correction of surface tension can increase the accuracy of Köhler curve. For ultra-small particles ( d  = ∼3 nm), the MMAS/DMAS have higher hygroscopic capacity than that of AS.